CHARACTER DEVELOPMENT MANAGEMENT OF COASTAL MADRASAH STUDENTS IN MA AL-WASHLIYAH, NAGUR VILLAGE, TANJUNG BERINGIN DISTRICT, SERDANG BEDAGAI REGENCY - Zainal Arifin; Muhammad Rifa’i; Muhammad Fadhli (SOSIOEDUKASI, 2026)
This study aims to analyze the management of student character development in a coastal madrasah at MA Al-Washliyah in Nagur Village, Tanjung Beringin District, Serdang Bedagai Regency. The focus of the study includes four main aspects: the management of character development through the introduction of moral concepts and character education values, the management of character habituation through repeated practices, the management of reflective activities, and the management of the integration of moral actions in a natural and consistent manner. This study employed a qualitative approach with a descriptive research design. Data collection techniques were conducted through in-depth interviews, direct observation, and document analysis, with the main informants consisting of the head of the madrasah, vice principal, teachers, and students. The results of the study indicate that character development at MA Al-Washliyah in Nagur Village has been managed in a planned and contextual manner in accordance with the characteristics of the coastal environment. The introduction of moral values is carried out through integration in the learning process, the exemplary behavior of educators, and the utilization of religious learning resources. Character habituation is implemented through consistent daily routines and continuous supervision. Reflection is conducted through dialogical approaches and counseling that help students understand the moral meaning of their actions. Furthermore, the integration of moral actions is reflected in students’ behavior, which becomes increasingly independent and consistent and is embodied in the school culture. This study concludes that the management of character development at MA Al-Washliyah in Nagur Village is implemented systematically and sustainably through the stages of introduction, habituation, reflection, and integration of moral values. However, the effectiveness of character development is still influenced by external factors, such as family and community environments. Therefore, strengthening the synergy between schools, families, and communities is necessary to ensure the sustainability of character education reinforcement for students in coastal madrasahs